VIEWING CONTRASTIVE RHETORIC FROM A POST MODERN PERSPECTIVE: FINDING AN IMPLICATION TO THE SECOND LANGUAGE WRITING PEDAGOGY - Susilo Susilo (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
The hybrid nature of culture that comes up as a result of postmodern world brings about considerable interaction, borrowing, and fusion between cultures and communicative genres. In such situation, there is erosion of national boundaries, greater multilingualism, and fluidity in identity; hence a" absolute construct of particular culture is getting blurred. Consequently, the term "native identity" has come to a "blurring spot" in the sense that it will be simply awkward to hold firmly one's native identity when multilingualism has become norm. This hybridand plural character of identity has gone to be considerable as the basis of contrastive texts analysis. The newest way of looking at the contrastive rhetoric is that differences in pragmatic or rhetorical expectations should not be considered as unproficiency or interference for the bi/multilingual writer, rather rhetorical choices opted by the bi/multilingual writer should be considered as critical/alternate discourse. This article is aimed to look at the pedagogy of shuttling between languages done by multilingual writers as the new orientation in the teaching and learning second language writing.